2018
DOI: 10.1177/0897190018766944
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Impact on Secondary Stroke Prevention

Abstract: Pharmacists can play a role in reducing risk factors for secondary stroke/TIA and prevent future hospital admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 14 publications
0
24
1
Order By: Relevance
“…Of the cluster randomized studies, one [ 26 ] was a sub-analysis of the completed study [ 25 ]. Three studies were of experimental before-and-after design [ 28 , 29 , 30 ], five were cross-sectional [ 31 , 32 , 33 , 34 , 35 ] and fourteen were cohort studies [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. To capture the breadth of pharmacist interventions, two audit reports [ 50 , 51 ] and five conference abstracts [ 23 , 33 , 40 , 41 , 47 ] were also included for data extraction although quality assessment was not possible using standard tools.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the cluster randomized studies, one [ 26 ] was a sub-analysis of the completed study [ 25 ]. Three studies were of experimental before-and-after design [ 28 , 29 , 30 ], five were cross-sectional [ 31 , 32 , 33 , 34 , 35 ] and fourteen were cohort studies [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. To capture the breadth of pharmacist interventions, two audit reports [ 50 , 51 ] and five conference abstracts [ 23 , 33 , 40 , 41 , 47 ] were also included for data extraction although quality assessment was not possible using standard tools.…”
Section: Resultsmentioning
confidence: 99%
“…Individual study characteristics are shown in Table 5 , Table 6 and Table 7 . Seven studies reported pharmacist interventions for primary stroke prevention [ 28 , 29 , 30 , 32 , 33 , 36 , 50 ] and twenty-four focussed on secondary stroke prevention [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 31 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 , 49 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have also contributed to related interventions including medication counselling, medication reconciliation or follow up, recommending initiation of therapy and preventing adverse drug reactions. [28,[52][53][54][55] Prescription and medication reconciliation errors during transitions of care are common, and sole responsibility of the pharmacist may not prevent medication errors. [56] Simple measures such as using mail order pharmacy instead of local pharmacy have showed improvement in medication adherence in the stroke population.…”
Section: Discussionmentioning
confidence: 99%